2019
DOI: 10.3390/resources8020106
|View full text |Cite
|
Sign up to set email alerts
|

Feed-in-Premium Renewable Energy Support Scheme: A Scenario Approach

Abstract: Topics such as energy demand, energy security and greenhouse emissions have made countries around the world turn to more environmentally friendly resources to produce electricity. Due to their stochastic behaviour (particularly wind energy and solar photovoltaics (PV)), the energy producers that are renewable energy driven need concrete financial mechanisms in order to sell their generated electricity under uncertainty in a highly competitive environment. In this work, the application of the Feed-in Premium (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In a separate study in Cyprus, Dimitriou et al (2020) [102] evaluated the energy and economic viability of various scenarios for a public office building, utilizing iSBEM and Design Builder. This research underscores the integration of energy and economic considerations in research, a well-established theme in energy-related discourse [103,104], often accompanied by policy analysis [105,106]. Their findings revealed that cooling, lighting, and equipment collectively contribute up to 85% of the total energy consumption in a typical office building in Cyprus.…”
Section: Discrepancies Between Real and Simulated Datamentioning
confidence: 68%
“…In a separate study in Cyprus, Dimitriou et al (2020) [102] evaluated the energy and economic viability of various scenarios for a public office building, utilizing iSBEM and Design Builder. This research underscores the integration of energy and economic considerations in research, a well-established theme in energy-related discourse [103,104], often accompanied by policy analysis [105,106]. Their findings revealed that cooling, lighting, and equipment collectively contribute up to 85% of the total energy consumption in a typical office building in Cyprus.…”
Section: Discrepancies Between Real and Simulated Datamentioning
confidence: 68%
“…A multiple revenue stream approach is given attention under this work. As both wind manufacturers and wind‐based utilities confront survival problems, a multiple revenue stream approach would offer an alternative business model, which, if followed, could act as a solid profitability plan.…”
Section: Introductionmentioning
confidence: 99%
“…Most European countries have chosen to accelerate the penetration of renewable energies into the electricity mix (20% by 2020). The production of electricity from renewable energy sources is supported by various support schemes [2][3][4]. To encourage the development of renewable energy sources, European countries have adopted a priority injection system that guarantees them access to the grid as soon as they produce electricity.…”
Section: Introductionmentioning
confidence: 99%